Pembinaan personaliti islamik dalam kalangan usahawan asnaf berjaya di negeri Selangor - Izatul Akmar, Ismail (2022)
This study focuses on Islamic personality development among successful asnaf entrepreneurs because research in this area is minimal. Among the main issues regarding asnaf entrepreneurs is the issue of attitude that drives their success and failure. Attitude is a component of an individual's personality. Hence, Islamic personality development is important in shaping asnaf entrepreneurs’ personalities. This study has three main objectives. First, identify the factors that influence successful asnaf entrepreneurs’ Islamic personality development. Second, exploring the Islamic personality traits of successful asnaf entrepreneurs. Third, analyse the implications of Islamic personality on asnaf entrepreneurs’ success. This study used a phenomenological-transcendental qualitative method involving seven iconic successful asnaf entrepreneurs in Selangor and Business Development Sector managers in TERAS. Data and information were collected by semistructured interviews and analysed using phenomenological methods assisted by Atlas.ti software version 8. The data validity and reliability were achieved using detailed study descriptions and expert reviews. The study found that internal factors tazkiyyah al-Nafs comprising mujahadah al-Nafs and riyadah al-Nafs and the support from external factors like family, related agencies, friends, mentors, and the community strengthen successful asnaf entrepreneurs’ identity. The results show some similarities in Islamic personality traits of successful asnaf entrepreneurs such as fathonah, amanah, siddiq, tabligh, diligent, persistent, friendly and charitable. Nonetheless, there are differences in Islamic personality traits which contribute to the success of asnaf entrepreneurs, namely determined, willful, firm but gentle. This study also found that Muslim entrepreneurs’ personality has implications on the asnaf entrepreneurs’ success from the aspect of changing asnaf’s status from a zakat recipient to a zakat payer, helping others in distress, and improving their living standards and sustenance. This study provides a significant contribution to knowledge relating to asnafs’ Islamic personality development and guidelines to related agencies in strengthening training aspects, especially in shaping the asnafs’ identity and personality to be independent.